Consequences of Power Abuse on learning Processes: Assessing the Impact of Power Abuse in Private Universities of Nangarhar, Afghanistan - Safi, Abdul Qayoum; Sapi, Abdul Manan; Kayen, Hazrat Shah (Papanda Publisher, 2024)
Abuse of Power harms the actions and effects of organizations, especially if the abuse occurs in educational institutions, the damage will be greater. In developing countries like Afghanistan, the possibility of abuse of power in private universities is high. This article focuses on the effects of power abuse in private universities in Nangarhar Afghanistan. The purpose of this study is to reveal examples of power abuse in private universities in the Nangarhar province of Afghanistan and to investigate its impact on the educational process. Novelty: In previous studies, only one type of abuse of power was mentioned in private universities in Nangarhar, while this study mentioned two types of abuse of power in private universities in Nangarhar1) abuse of power by lecturers 2) abuse of power by senior management staff. Also, another improvement of this research to the previous research is that the researcher tried to interview the affected students and university staff about the topic and clarify the topic based on these interviews. For this research, the authors use a qualitative approach with case-study methods. This study presents cases of power abuse in private higher education institutions in Nangarhar, Afghanistan. The researcher conducted interviews with students, administrative staff, and lecturers of private universities in eastern Afghanistan. As a result, the study found that there are two types of power abuse in private universities in Nangarhar, abuse of power by lecturers and abuse of power by senior management staff.